Implementación de una red voz-ip para mejorar la comunicación entre departamentos de la Unidad De Estudios a Distancia de la Universidad Técnica Estatal de Quevedo. - Guamán Delgado, Luis Carlos (2015)
Communication in humans is natural since the beginning of the rational species. The telegraph was the first revolution in communication with the Morse code which allowed communication over long distances, then the phone is new, as over time the way people communicate has constantly evolved, today the advancement of technology allowed to use the Internet for communication regardless of distance, and for that we have developed different forms remains one of the most widely used IP communication, it allows carry voice and image with various multimedia applications reliably and securely. So telecom is the service of all human beings and have the internet service is only necessary to install a PBX Voice-IP to not depend on fixed telephony. For this work it has taken into account the requirements and needs of users Schooling Unit of the State Technical University of Quevedo. Therefore the main objective of the project to implement a Voice-IP network, for it was necessary to design the network diagram according to the needs of the UED UTEQ. The technique used was the design and implementation of software, the materials used were phone Grandstream GXP 1400, UTP cat.6, elastix server and other equipment such as switch, router, work is of interest and relevance today, the conclusion that was reached was that free software Elastix 2.4.0 is stable because it allows an exchange dimension depending on the requirements and needs of the user.